PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TEKNIK KANCING GEMERINCING TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII MTsN PALANGKI - Mursyida, Mursyida; Anggraini, Villia; Mardiyah, Ainil (STKIP PGRI Sumbar, 2013)
This research based of the lack of the studentsâ comprehension of mathematics concepts. This condition can be shown from studentsâ mathematics achievements of class VIII MTsN Palangki of Sijunjung Regency in 2013/2014 Academic Year. The purpose of this research to find out the effectivity of the application of cooperative learning technique Kancing Gemerincing toward the comprehension of studentsâ mathematical concepts andÂ influence of the application of cooperative learning technique Kancing Gemerincing toward the comprehension of studentsâ mathematical concepts. This research is kind of experimental research with the design random on the subject. The population of this research is students in class VIII that consist of 6 classes. The instrument that was used in this research is observation of student activity sheets and post test in form ofÂ essays with reliability of the test is 0.855. Technique of data analysis is using one side T- Test with MINITAB. The result of hypothesis test is gotten that P-value 0.016 is smaller than Î± that is 0.05, so the research hypothesis can be accepted. Consequently, it can be concluded that the students comprehension of mathematical concepts with the application of cooperative learning technique Kancing Gemerincing is better than conventional learning in the class VIII of MTsN Palangki of Sijunjung Regency.